EFFECTIVE IONIC RADIUS OF Y3+ DETERMINED FROM LATTICE-PARAMETERS OF FLUORITE-TYPE HFO2 AND ZRO2 SOLID-SOLUTIONS - KIM, DJ; HYUN, SH; KIM, SG; YASHIMA, M (AMER CERAMIC SOC, 1994)
Fluorite-type HfO2 and ZrO2 solid solutions were prepared by doping with 8 to 14 mol% of Ho2O3 and Y2O3, and their lattice parameters were determined. In both HfO2 and ZrO2 systems, the lattice parameters of the solid solutions containing Ho2O3 were consistently greater than those containing the same amounts of Y2O3. This indicated that the ionic radius of Ho3+ was larger than that of Y3+ in the fluorite structure solid solutions. The effective ionic radius of Y3+ in eightfold coordination was estimated to be 0.1011 nm by using the measured lattice parameters and the empirical equations to predict the lattice parameters of the fluorite-type solid solutions.
Keywords: DEFECT CLUSTERS; ELECTROLYTES; CONDUCTIVITY